WinClastour—a Visual Basic program for tourmaline formula calculation and classification - Yavuz, Fuat; Yavuz, Vural; Şaşmaz, Ahmet (My University, 2006)
WinClastour is a Microsofts Visual Basic 6.0 program that enables the user to enter and calculate structural formulae of tourmaline analyses obtained both by the electron-microprobe or wet-chemical analyses. It is developed to predict cation site-allocations at the different structural positions, as well as to estimate mole percent of the end-members of the calcic-, alkali-, and X-site vacant group tourmalines. Using the different normalization schemes, such as 24.5 oxygens, 31 anions, 15 cations (T+Z+Y), and 6 silicons, the present program classifies tourmaline data based on the classification scheme proposed by Hawthorne and Henry [1999. Classification of the minerals of the tourmaline group. European Journal of Mineralogy 11, 201–215]. The present program also enables the user Al–Mg disorder between Y and Z sites. WinClastour stores all the calculated results in a comma-delimited ASCII file format. Hence, output of the program can be displayed and processed by any other software for general data manipulation and graphing purposes. The compiled program code together with a test data file and related graphic files, which are designed to produce a high-quality printout from the Grapher program of Golden Software, is approximately 3Mb as a self-extracting setup file.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Tourmaline; Wet-chemical; Classification; Al–Mg disorder; Electron-microprobe; Normalization